Twin sowing and summer sowing: Alternative techniques to introduce legumes into pastures - Loi A.; Nutt B.J. (The contributions of grasslands to the conservation of Mediterranean biodiversity, 2010)
Twin sowing and summer sowing are two techniques that are being evaluated as a means to introduce legume species into pastures. Both methods utilise in the first instance legume seed dormancy to prevent undesirable germination and secondly the breakdown of this dormancy to provide an adequate number of germinating seed under favourable conditions. They are being developed to enable a cost effective and convenient means to improve pasture production and quality using low cost seed produced on farm. Twin sowing refers to sowing legume seed with a cereal or oilseed crop in a dormant form so that little germination occurs under the crop. With field exposure over the following summer and autumn, the hardseed dormancy will breakdown and produce germinating seeds. Summer sowing is similar but requires a sowing operation in the summer or autumn following crop harvesting and uses the same principle of hardseed breakdown for legume establishment. In both cases the pasture legume will establish as regenerating pasture using full use of the growing season. These two techniques have the potential to reduce the cost of the pasture legume establishment, particularly for species such as serradella where seed processing to enhance germination is difficult and costly.
13. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM International Network for the Research and Development of Pasture and Forage Crops, 2010/04/07-10, Alicante (Spain)